2012
DOI: 10.1088/0953-8984/24/33/336007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of atomic anti-site disorder and ferrimagnetic order in the half-metallic Heusler alloy Mn2V Ga

Abstract: The band structure calculation for the compound Mn(2)VGa carried out using the plane wave self-consistent field package with generalized gradient approximation shows that the compound is nearly half-metallic at the equilibrium lattice parameter. However, theoretical investigations have shown that a certain percentage of atomic anti-site disorder can destroy the half-metallic nature of the sample. Hence it is important to quantify the site disorder in these systems. We have deduced the percentage of atomic anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(37 reference statements)
2
4
0
Order By: Relevance
“…which is close to the S-P value. The obtained moment value is in agreement with the earlier report [18].…”
Section: Ab Initio Studies On Mn 2 V 1−x Cosupporting
confidence: 93%
See 1 more Smart Citation
“…which is close to the S-P value. The obtained moment value is in agreement with the earlier report [18].…”
Section: Ab Initio Studies On Mn 2 V 1−x Cosupporting
confidence: 93%
“…Earlier ND studies showed that Mn 2 VGa alloy crystallizes in the cubic L2 1 structure [18]. Therefore in our previous report on the structural and magnetic properties of the Mn 2 V 1−x Co x Ga (x = 0, 0.25, 0.5, 0.75, 1) alloys, Rietveld refinement of XRD patterns was carried out by assuming the L2 1 structure.…”
Section: Neutron Diffraction Studies On Mnmentioning
confidence: 99%
“…But for the A2 disorder, all three scattering terms would become equal causing the absence of both the superlattice reflections. However the earlier report on the neutron diffraction studies of Mn 2 VGa alloy has shown the presence of huge superlattice reflections even though they were absent in the XRD pattern [19]. They attributed the lack of these peaks in the XRD pattern to the similar atomic scattering factors of x-ray for the elements Mn,V and Ga.…”
Section: Figure 1(a) Shows the X-ray Diffraction (Xrd) Patterns (Usingmentioning
confidence: 88%
“…is comparable with the earlier reported value of 1.85 µ B /f.u. [19]. The small deviation of experimental magnetic moments from the S-P value could be due to the atomic anti-site disorder present in the system.…”
Section: Magnetic Propertiesmentioning
confidence: 92%
See 1 more Smart Citation